The Relationship of Puddle Conditions and The Incident of Malaria in Waimaringi Village, Kodi Balaghar District, Southwest Sumba, East Nusa Tenggara - Suhardin musa ibrahim; Ukik Agustina (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2024)
Malaria has been a health issue recently that can cause death. The high incidence of malaria is closely related to several factors. Such as during the rainy season where spring water flows stagnant, in puddles of rainwater on the ground, and in rock holes. In the dry season, groundwater sources decrease, causing puddles to form along rivers. These puddles of water are used as breeding places. The aim of the research is to determine the relationship between puddle water conditions and the incidence of malaria in Waimaringi Village. The type of research used was analytical observational with a cross-sectional approach. Population size 800 respondents. The sample was selected using purposive sampling, totaling 267 respondents. Data analysis used bivariate analysis with the Chi Square test at a significance level of α ≤ 0.05. The research results were found to be significant at 0.000 or smaller than 0.05, so H0 was rejected and H1 was accepted where there was a relationship between puddle water conditions and the incidence of malaria in Waimaringi Village.